Endometrial and Ovarian Cancer in Lynch Syndrome - Crispens, Marta Ann (Clinics in Colon and Rectal Surgery, 2012)
Lynch syndrome (LS) is an autosomal dominant familial cancer risk syndrome that occurs due to a germline mutation in one of several mismatch repair genes and is associated with an increased risk of colorectal, endometrial, and ovarian cancer. The risk of endometrial cancer equals or exceeds that of colorectal cancer in women with LS. The diagnosis of gynecologic cancer precedes that of colorectal cancer in over half of women with metachronous gynecologic and colon cancers, making gynecologic cancer a “sentinel cancer” for LS. There are no studies addressing the effectiveness or safety of chemoprevention for women with LS. Surveillance with gynecologic examination including assessment of symptoms, transvaginal pelvic ultrasonography, endometrial biopsy, and CA125 tumor marker assessment can be offered, but has not been shown to improve outcomes for these patients. Prophylactic hysterectomy with bilateral salpingo-oophorectomy performed after the completion of childbearing may be offered for gynecologic cancer prevention.
Keywords: Lynch syndrome; endometrial cancer; ovarian cancer; surveillance; prophylactic surgery